Estrogen actions on glial reactivity and inflammation-mediated memory impairment: sex differences and interaction with other neurotrophic factors - Bellini, María José (2015)
There is growing evidence that documents profound effects of estrogens on learning, memory, and mood as well as neurodevelopment and neurodegenerative diseases. However, the ability of estradiol to influence synaptic plasticity, neurotransmission, neurodegeneration and cognition, could be different depending on sex dimorphisms. It emerges that estrogens have different, even opposite, effects as well as similar effects in male and female brains. The protective effects of estradiol on neural cells are mediated in part by modulation of neurotrophic factors such as insulin like growth factor (IGF-l), tyrosine kinase A (Trk A), nerve growth factors (NGF), and the like. Also, it modulates the action of neurotrophins, which in turn regulate the synaptogenesis, synaptic plasticity and synaptic functions. By these actions estrogen prevents or slows down the neurodegenerative process. Another described effect of estradiol is the capacity to modulate inflammatory response mediated by glial cells. Neuroinflammation is a feature not only of many neurological disorders but also of aging, and it is accompanied by activation of glial cells and the release of proinflammatory cytokines and chemokines. Such activation is a normal response oriented to protect neural tissue. However, excessive and chronic activation of glia may lead to neurotoxicity and may be harmful for neural tissue. Estrogenic compounds may be candidates to counteract brain inflammation under neurodegenerative conditions by targeting the production and release of proinflammatory molecules by glial cells. In this chapter we will review different mechanisms that may be implicated in the diverse actions of estradiol, the differences according to gender and we empathize in the anti-inflammatory action on glial cell. We will also explore the interaction of estradiol with others neurotrophic factors, such as IGF-I in the regulation of neurodegeneration and memory impairment. Finally, the possibility of using selective estrogen receptor modulators (SERMs) to exert estradiollike neuroprotective actions in the brain as an alternative to estrogen will be discussed.